The physiological responses of critically endangered species Ardisia gigantifolia Stapf (Primulaceae) to different light intensities - R. LIU; X.E. NING; D.M. LI; L. CHEN; Z.L. NING (Photosynthetica, 2023)
To investigate the light intensity suitable for the growth of Ardisia gigantifolia Stapf, morphology, photosynthetic parameters, and indicators of oxidative stress were analyzed under different light intensities. Compared to high-irradiance treatment, medium and low-irradiance treatments promoted plant growth and restricted transpiration. Compared to medium irradiance, plants under high and low irradiance exhibited significantly lower maximal photochemical efficiency, potential photochemical efficiency, and electron transport rate, but significantly higher malondialdehyde content. This indicated that both excessive light and severe shading inhibited photosynthetic activity and induced oxidative stress, which resulted in a significant decrease in net photosynthetic rate. A. gigantifolia can adapt to different light intensities, improving light harvesting and utilizing capacity under low irradiance by increasing Chl (a+b) content and reducing Chl a/b ratio, and adapting to high irradiance by enhancing heat dissipation and activity of peroxidase. A. gigantifolia showed the best performance in growth and photosynthesis under medium irradiance treatment.